The Effective Management of the Village of the Five Precepts Project - เศรษฐนันท์, พระรัฐวุฒิชัย (Journal of Educational Review Faculty of Education in MCU, 2019)
The Village of the five precepts project was the project that conducts by Sangha and public and focus on the empirical achievement. Achievements of project were the Buddhist live along with the five precepts and five Dhamma, peace of mind and unity. The operation of the project must manage systematically to achieve. The project management includes leadership, guiding, motivation, communication, planning and management affect to the effective management of the village of the five precepts project.